2014
DOI: 10.1177/1538192714556892
|View full text |Cite
|
Sign up to set email alerts
|

Belonging in the Academy

Abstract: This action research study, supported by a quantitative data analysis, presents a counternarrative to the deficit discourse regarding Latino/a First Time in Any College (FTIAC) departure during the first year of college. It argues that an intentional learning community model, that is culturally and linguistically responsive to Latino/a student needs, can produce significant gains in first-to second-year retention rates and better predicts retention than either high school grade point average or standardized te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
(26 reference statements)
7
18
0
Order By: Relevance
“…This study lends support to previous recommendations for student support, orientation, and educational services programs (S. M. Gonzalez et al, 2015;Pérez & Ceja, 2010;Rodriguez et al, 2015;Zalaquett, 2005). First, community college-university joint programs should establish culturally specific programs for Latina/o students to focus on the following objectives: (a) building community and interconnected networks between Latina/os, (b) providing culturally aware counselors and mentors who understand Latina/o identities and needs, and (c) instilling appreciation of Latina/o culture and diversity.…”
Section: Recommendations and Conclusionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study lends support to previous recommendations for student support, orientation, and educational services programs (S. M. Gonzalez et al, 2015;Pérez & Ceja, 2010;Rodriguez et al, 2015;Zalaquett, 2005). First, community college-university joint programs should establish culturally specific programs for Latina/o students to focus on the following objectives: (a) building community and interconnected networks between Latina/os, (b) providing culturally aware counselors and mentors who understand Latina/o identities and needs, and (c) instilling appreciation of Latina/o culture and diversity.…”
Section: Recommendations and Conclusionsupporting
confidence: 87%
“…In addition, several studies explain that culturally rich environments, particularly those that embrace, celebrate, and affirm Latina/o culture, help students persist and succeed (Gloria & Segura-Herrera, 2004;Nora & Crisp, 2009;Pérez & Ceja, 2010;Rendón, 2002). Culturally sensitive environments instill a sense of belonging and the feeling of having a home away from home at school that positively influences students' integration and motivation (K. P. González, 2001;S. M. Gonzalez et al, 2015;Hurtado, 2002;Rendón, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions focused on Latino/Latina students with an emphasis on building a supportive peer community, helping students identify social and academic resources, and develop skills in balancing their home and university responsibilities resulted in better social adjustment and critical consciousness than students who were not exposed to the intervention (Cerezo & McWhirter, 2012). Similarly, in a recent intervention study, Gonzales et al (2015) found that by creating a sense of familia between students and the faculty and staff and requiring students to enroll in first-year English and math courses as a cohort, Latino/ Latina students experienced a rise in first-to second-year retention rates.…”
mentioning
confidence: 94%
“…A sense of belonging buoyed by sociocultural interactions and peer support can be important to students' decisions to continue their studies at a university (Cerezo & McWhirter, 2012;Gonzales, Brammer, & Sawilowsky, 2015). Interventions focused on Latino/Latina students with an emphasis on building a supportive peer community, helping students identify social and academic resources, and develop skills in balancing their home and university responsibilities resulted in better social adjustment and critical consciousness than students who were not exposed to the intervention (Cerezo & McWhirter, 2012).…”
mentioning
confidence: 99%